2010
DOI: 10.1007/978-3-642-10613-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Biology of Sulfur and Its Functions in Plants

Abstract: Sulfur is one of the most versatile elements in life. It functions in fundamental processes such as electron transport, structure, and regulation. In plants, additional roles have developed with respect to photosynthetic oxygen production, abiotic and biotic stress resistance and secondary metabolism. Sulfate uptake, reductive assimilation, and integration into cysteine and methionine are the central processes that direct oxidized and reduced forms of organically-bound sulfur into its various functions. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 258 publications
(288 reference statements)
0
13
0
Order By: Relevance
“…Bacteria take it up as sulfate or thiosulfate compounds, and thiosulfate assimilation in bacteria has been extensively studied (Ghosh and Dam 2009). Although fragmented information can be found on thiosulfate in plants, reviews and research articles on the biochemistry and molecular biology of plant sulfur metabolism scarcely refer to it, reflecting a lack of knowledge on its importance to cell metabolism and to regulation of plant growth (Hell et al 2010;Yi et al 2010;Mugford et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria take it up as sulfate or thiosulfate compounds, and thiosulfate assimilation in bacteria has been extensively studied (Ghosh and Dam 2009). Although fragmented information can be found on thiosulfate in plants, reviews and research articles on the biochemistry and molecular biology of plant sulfur metabolism scarcely refer to it, reflecting a lack of knowledge on its importance to cell metabolism and to regulation of plant growth (Hell et al 2010;Yi et al 2010;Mugford et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The S reduction pathway is well characterized and conserved among different plant species. However, the major site of S reduction varies and might be dependent on environmental conditions and plant species (Rennenberg et al, 1979;Brunold and Suter, 1989;Hopkins et al, 2005;Hawkesford and De Kok, 2006;Hell et al, 2010). Following translocation of sulfate in the xylem transpiration stream, S reduction predominantly occurs in mature source leaves (Rennenberg et al, 1979;Bourgis et al, 1999;Lappartient et al, 1999;Hopkins et al, 2005), although in legumes, S reduction also takes place in other organs.…”
mentioning
confidence: 99%
“…Sulfur is a constituent of the amino acids cysteine (Cys) and methionine (Met) which are necessary for the synthesis of proteins and serve as precursors of important cofactors and sulfur containing secondary metabolites ( Thomas et al, 2000 ; Mugford et al, 2011 ). The metabolites of sulfate assimilation and metabolism have important effects on plant growth, development, environmental response, resistance to biological and abiotic stress, crop quality and yield ( Zhao et al, 1999 ; Hell et al, 2010 ; Gironde et al, 2014 ). Recent studies have suggested that sulfur containing compounds may also play a role in regulation of stomatal movement.…”
Section: Introductionmentioning
confidence: 99%